The Effect Of Extensible Business Reporting Language (Xbrl) Implementation And Corporate Governance On Tax Avoidance - Fatmawati, Fira; Harris, Lutfi (Reviu Akuntansi, Keuangan, dan Sistem Informasi, 2025)
The unachieved tax revenue realization target indicates low tax compliance and reflects companies' potential for aggressive tax avoidance. As such, this study aims to analyze and obtain empirical evidence of the effect of XBRL implementation and corporate governance mechanisms consisting of managerial ownership, institutional ownership, independent commissioners, and audit committees on tax avoidance. This study applies a quantitative approach involving secondary data from the financial statements and annual reports of companies listed on the LQ45 index of the Indonesia Stock Exchange (IDX) during the period of 2016-2023. The samples include 11 companies selected through purposive sampling, analyzed by panel data regression processed by Eviews 12. The study results exhibit that XBRL implementation and independent commissioners hurt tax avoidance, while managerial ownership, institutional ownership, and audit committees do not affect tax avoidance. Companies and regulators may consider the findings of this study for making decisions and regulations related to the implementation of XBRL, corporate governance, and taxation policies.